Development of a Mathematics Student Worksheet Using SketchUp Based on a Project-Based Learning Approach - Thofan, Angre Andes; Ilmi, Zainal; Sasalia S, Putri; Wulan, Endah Nawang; Pirdaus, Muhammad Miftahul; Anugrah, Siti Dian (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2025)
This research focuses on the development of a SketchUp-based student worksheet using a project-based learning approach to support geometry learning in junior high school. The study responds to the lack of visual media in conventional mathematics instruction, particularly in representing three-dimensional objects. The development process followed the 4D model: Define, Design, Develop, and Disseminate. At the Define stage, a needs analysis revealed students’ difficulties in spatial reasoning and their preference for visual learning. SketchUp was selected for its capability to model 3D objects interactively. The product was validated by two experts, resulting in an average score of 89% for content and 87% for media, both categorized as “very feasible.” A limited trial involving 18 ninth-grade students showed an average feasibility score of 80.3%, indicating positive student responses. Although some improvements are needed in the clarity of instructions, the integration of SketchUp and project-based learning shows potential to enhance student engagement and learning experiences in geometry. The study supports the development of innovative, curriculum-aligned digital learning media.